The influence of local government policy on the cultural wisdom of noken use by civil servants (ASN) on the productivity and income of papuan women noken artisans in Mimika Baru District, Mimika Regency - Andreas Aula; Hasan Basri Umar; Yundy Hafizrianda (Journal of Multidisciplinary Academic and Practice Studies, 2024)
Purpose: This study examines the influence of local government policy mandating noken use among civil servants (ASN) on the productivity and income of mama-mama Papua artisans in Mimika Baru District, Mimika Regency. The policy aims to preserve cultural heritage while enhancing the economic empowerment of Papuan women through the traditional craft of noken, recognized by UNESCO as intangible cultural heritage Research/methodology: The research employed a quantitative survey approach with 35 respondents selected through accidental sampling from a population of 350 artisans. Data were collected via questionnaires, interviews, and observations, and analyzed using Path Analysis supported by SPSS software Results: The findings indicate that the noken use policy has a positive and significant effect on both artisan productivity (coefficient = 0.3524; p = 0.0379) and income (coefficient = 0.2846; p = 0.0442). The policy has increased demand, encouraging higher production, better product quality, and improved selling prices. However, 54% of artisans still fall within the low-income category, earning below IDR 1,450,000 per month. Conclusions: While the policy supports cultural preservation and economic growth, artisans continue to face challenges such as limited market access, lack of regeneration among younger artisans, and inadequate training. Limitations: The study is geographically limited to one district and focuses only on productivity and income. Contribution: This research highlights the role of cultural wisdom-based policies in strengthening creative economies and suggests entrepreneurship training, digital marketing, and improved distribution facilities as complementary strategies.